Implementation of Humanistic Education in Shaping to a Moderate Attitude in Elementary Schools - Musthofa, Musthofa; Nasikhin; Ahmad Zahiruddin Mohd Zabidi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study analyzes the implementation of humanistic education in shaping a moderate attitude among elementary school students within the broader context of promoting religious moderation and critical citizenship. The research aims to explore how humanistic education contributes to fostering critical thinking, collaboration, innovation, and democratic values at the elementary level. Employing a qualitative method, data were collected through in-depth interviews, observations, documentation studies, and surveys involving 54 students, four teachers, and three parents from two elementary schools in the Batang Regency. Thematic analysis was utilized to identify patterns across the collected data. The findings demonstrate that humanistic education strengthens students' intellectual capacities through 4C-based learning (Creativity and Innovation, Collaboration, Communication, Critical Thinking, and Problem-Solving) and enhances humanitarian and democratic narratives embedded within character education programs. Survey results revealed high percentages of nationalist attitudes (93.3%), tolerance (90.6%), non-violent tendencies (93.3%), and cultural adaptability (89.75%) among students. The study concludes that integrating humanistic education with religious moderation efforts significantly shapes moderate attitudes in young learners. These findings imply that educational institutions should systematically adopt humanistic approaches to cultivate moderate, tolerant, and critically engaged citizens from an early stage.